Helminth Regulation of Immunity: A Three-pronged Approach to Treat Colitis. Issue 10 (October 2016) - Lopes, Fernando; Matisz, Chelsea; Reyes, José L.; Jijon, Humberto; Al-Darmaki, Ahmed; Kaplan, Gilaad G.; McKay, Derek M.
Abstract : Abstract: By reputation, the parasite is a pariah, an unwelcome guest. Infection with helminth parasites evokes stereotypic immune responses in humans and mice that are dominated by T helper (Th)-2 responses; thus, a hypothesis arises that infection with helminths would limit immunopathology in concomitant inflammatory disease. Although infection with some species of helminths can cause devastating disease and affect the course of microbial infections, analyses of rodent models of inflammatory disease reveal that infection with helminth parasites, or treatment with helminth extracts, can limit the severity of autoinflammatory disease, including colitis. Intriguing, but fewer, studies show that adoptive transfer of myeloid immune cells treated with helminth products/extracts in vitro can suppress inflammation. Herein, 3 facets of helminth therapy are reviewed and critiqued: treatment with viable ova or larvae, treatment with crude extracts of the worm or purified molecules, and cellular immunotherapy. The beneficial effect of helminth therapy often converges on the mobilization of IL-10 and regulatory/alternatively activated macrophages, while there are reports on transforming growth factor (TGF)-β, regulatory T cells and dendritic cells, and recent data suggest that helminth-evoked changes in the microbiota should be considered when defining anticolitic mechanisms. We speculate that if the data from animal models translate to humans, noting the heterogeneity therein, then the choice between use of viable helminth ova, helminth extracts/molecules or antigen-pulsed immune cells could be matched to disease management in defined cohorts of patients with inflammatory bowel disease. Abstract : Article first published online 26 August 2016.